Cross-Cultural Perspectives on Policy and Practice : Decolonizing Community Contexts. - Lavia, Jennifer (Routledge Research in Education, 29., 2009)
This book provides a space in which struggles for Indigenous Knowledge within communities are articulated, valued, heard, and responded to. The contributors develop critical understandings of the implications of changing policy and practice for those within and working with the educational organisations and communities.